2020
DOI: 10.1159/000508487
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 in Pregnancy: A Clinical Management Protocol and Considerations for Practice

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has represented a major impact to health systems and societies worldwide. The generation of knowledge about the disease has occurred almost as fast as its global expansion. The mother and fetus do not seem to be at particularly high risk. Nevertheless, obstetrics and maternal-fetal medicine practice have suffered profound changes to adapt to the pandemic. In addition, there are aspects specific to and gestation that should be known by specialists in order to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
132
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(141 citation statements)
references
References 27 publications
(44 reference statements)
1
132
0
8
Order By: Relevance
“…Previous studies suggested that pregnant women are not more susceptible to SARS-CoV-2 infection than the general population [ 6 ]. However, the presence of comorbidities (e.g., diabetes and chronic hypertension), which often appear in the second trimester of pregnancy [ 7 , 8 ], as well as increased maternal age and high BMI may increase their risk of developing severe COVID-19 symptoms [ 8 ]. A report published on 26 June 2020 mentioning that 8207 pregnant women were confirmed to have SARS-CoV-2 infection altered this perception as it revealed that pregnant women may have an increased risk of developing severe symptoms of COVID-19 as compared to nonpregnant patients [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that pregnant women are not more susceptible to SARS-CoV-2 infection than the general population [ 6 ]. However, the presence of comorbidities (e.g., diabetes and chronic hypertension), which often appear in the second trimester of pregnancy [ 7 , 8 ], as well as increased maternal age and high BMI may increase their risk of developing severe COVID-19 symptoms [ 8 ]. A report published on 26 June 2020 mentioning that 8207 pregnant women were confirmed to have SARS-CoV-2 infection altered this perception as it revealed that pregnant women may have an increased risk of developing severe symptoms of COVID-19 as compared to nonpregnant patients [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severely ill patients between 32 to 34 weeks of gestation (or beyond) with COVID-19 pneumonia may benefit from early delivery. 24,30 These patients in ICU should be considered for thromboprophylaxis with low molecular weight heparin (LMWH). 31…”
Section: Management Of Covid-19-positive Women During Pregnancymentioning
confidence: 99%
“…20 Fetal monitoring should be done by electronic fetal monitoring (EFM) using CTG. 30 Efforts made to minimize the number of staff members entering the room, and units should develop a local policy specifying essential personnel for emergency scenarios. Asymptomatic birth partners asked to wash their hands frequently.…”
Section: Care During Labormentioning
confidence: 99%
See 1 more Smart Citation
“…Some experts even say that low-risk pregnant women infected with COVID-19 mild disease do not need clinical assessment and may follow the standard prenatal care and be safely isolated at home [12]. However, experts recommend frequent telehealth prenatal controls; hence COVID-19 patients may have sudden clinical deterioration [13].…”
Section: Findings and Analysismentioning
confidence: 99%